Additional Nata de Coco on The Performance of Cassava Starch Based Bioplastic - Febia Rini; Yulneriwarni Yulneriwarni; Endang Sukara (Journal of Tropical Biodiversity, 2022)
Bioplastics, an environmental friendly materials, attracting interest to many scientists around the world. Cassava starch may used as a major ingredient for bioplastics production. The addition of cellulose could improve the quality of starch base bioplastics. Cellulose used for thispurpise is mainly extracted from wood. Extraction of cellulose from wood materials is not easy. Removing contaminant particularly lignin is the major obstacle. The use nata de coco, a pure crystalline cellulose, may of great choice to replace cellulose of wood origin. It is the aim of this study to search the possibility of using nata de coco as filler replacing cellulose of wood origin for the production of bioplastic using cassava starch. The effect of nata de coco as a filler on the quality of bioplastics was studied using a Central Composite Design (CCD) and Response Surface Analysis (RSA). The ratio of tapioca and nata de coco and the ratio of nata de coco and glycerol were evaluated. The performance of bioplastics was measured semi qualitatively based on the structure, color, and its similarity to synthetic plastics. The result shows that the quality of bioplastics affected by nata de coco linearly when the maximum of nata de coco used up to 40% (v / v). Bioplastics may be prepared using 10% (w / v) tapioca, 3% (w / v) glycerol and 40% (v / v) nata de coco. The average degree of swelling of bioplastics is 18.75%, an average tensile test of 0.01494 kgf / mm2 and an average elongation 14.4056%. The results of this study indicate that nata de coco may be used as a filler in the manufacture of starch-based bioplastics re placing wood based cellulose.